Edge localized mode suppression and plasma response using mixed toroidal harmonic resonant magnetic perturbations in DIII-D. (4th January 2019) - Gu, S.; Sun, Y.; Paz-Soldan, C.; Nazikian, R.; Jia, M.; Wang, H.H.; Guo, W.; Liu, Y.Q.; Abrams, T.; Cui, L.; Evans, T.; Garofalo, A.; et al.
Abstract: Edge localized mode (ELM) suppression has been achieved in the DIII-D tokamak using mixed toroidal and 3 harmonic resonant magnetic perturbations (RMPs). Here is the toroidal mode number. It is observed that mixed toroidal harmonic RMPs lower the threshold current for ELM suppression compared to the single case. The decreased threshold suggests that mixed toroidal harmonic RMPs offer a better path to ELM control. The error field effect is studied by superimposing error field correction upon the phase scan, which shows that it is possible to suppress the ELM and correct the error field simultaneously. The plasma response measured by magnetic sensors shows the harmonic plays a key role in ELM suppression using mixed toroidal harmonic RMPs. A nonlinear jump in the plasma response is observed during the bifurcation from mitigation to suppression of ELMs, similar to the results reported in Nazikian et al (2015 Phys. Rev. Lett . 114 5). Magneto-hydrodynamic simulations using toroidal rotation find good agreement with the ELM mitigated phase when the input rotation profile is high and induces strong screening of the RMP. Simulations with zero-crossing rotation find strong penetration of the RMP and reproduce the mode structure of ELM suppression on both the low and high field side. This suggests that edge components may penetrate during the transition from ELM mitigation to suppression.